Embracing diversity in adult education: creating an inclusive environment for Turkish-speaking newcomers in community settings - Emel Kiliç; Wolfgang Jacquet (Humanities & Social Sciences Communications)
Abstract The integration of Turkish-speaking migrants into Belgian society presents multifaceted challenges, particularly concerning language acquisition and cultural adaptation. Despite Belgium’s multicultural landscape, newcomers often struggle with learning local languages, hindering their integration and limiting their opportunities in the labour market. This study aimed to explore the critical role of language proficiency and cultural understanding in the integration process, aiming to provide insights into effective integration strategies for Turkish-speaking migrants in Belgium. The research involved 59 Turkish-speaking participants from a mixed social integration course, divided into six focus groups. Additionally, in-depth interviews with 14 experts provided insights into the integration process, highlighting their experiences, expectations, challenges, and ambitions. Key findings indicate that language barriers and cultural differences impede integration, underscoring the need for tailored language training and professional development courses. Informal gatherings and focus groups emerged as effective tools for providing peer support, fostering mutual understanding, and addressing cultural anxieties. The study also identified the limitations of current integration efforts, noting that highly educated migrants adapt more easily due to their openness to new challenges and previous language learning experiences. However, those from closed communities, particularly women with low education levels, face significant barriers due to limited access to support services. By analysing individual perspectives and expectations of Turkish-speaking migrants, this study offers practical insights to inform the development of both formal and informal integration strategies. These findings highlight the importance for policymakers and community leaders to comprehend the challenges encountered by Turkish migrants, guiding the creation of tailored interventions to facilitate their successful integration into the host country, and ultimately contributing to a more inclusive and cohesive society.